Acoustical sensing and imaging - Lee, Hua, 1952- (CRC Press, Taylor & Francis Group, 2016)
"For complex operating modalities and dimensionalities, the design and development of high-performance sensing and imaging systems represent the most direct and significant advances in the field of system analysis and signal processing. In this field, the core components are physical modeling, mathematical analysis, formulation of image reconstruction algorithms, performance evaluation, and system optimization. Acoustical Sensing and Imaging covers the full scope of these compontents with an emphasis on the application of system analysis and signal processing in acoustical sensing and imaging." --back cover
Keywords: Acoustic imaging.; Remote sensing.; System analysis.; Signal processing -- Digital techniques.; elektronické knihy; electronic books